1985
DOI: 10.1021/ma00148a046
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular diffusion and the autoadhesion of polybutadiene

Abstract: A determination of the self-diffusion constant of polybutadiene was obtained from small-angle neutron scattering experiments. By ensuring that intimate contact was achieved between plied sheets of the polybutadiene, measurements were made of the diffusion of macromolecules across the interface as reflected by the development of adhesive forces at this interface. It was found that the increase in adhesion occurred over a much longer time scale than would be predicted from the measured values of the self-diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 4 publications
1
32
0
Order By: Relevance
“…33 However, the time required for development of adhesion in such experiments has been found to be substantially longer than the time calculated from the linear diffusion constant. 33,34 Another manifestation of retarded reentanglement is the equilibration time after removal of the solvent from polymer solutions. Colby et al 35 reported that a 1,4-polybutadiene with a M w exceeding 16 million dalton, for which the terminal relaxation issue was calculated to be 4.4 days, had not attained an equilibrium state even one month after drying.…”
Section: ■ Discussionmentioning
confidence: 99%
“…33 However, the time required for development of adhesion in such experiments has been found to be substantially longer than the time calculated from the linear diffusion constant. 33,34 Another manifestation of retarded reentanglement is the equilibration time after removal of the solvent from polymer solutions. Colby et al 35 reported that a 1,4-polybutadiene with a M w exceeding 16 million dalton, for which the terminal relaxation issue was calculated to be 4.4 days, had not attained an equilibrium state even one month after drying.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Once the reptation time is identified, it is easy to calculate the self-diffusion coefficient (D). Accordingly, at 25 • C the self-diffusion coefficient (D) values of B and BCLNA8 can be calculated from the equation given below [33]:…”
Section: Frequency Sweep Studiesmentioning
confidence: 99%
“…For pre-cure times equal to or less than 20 min, the measured strength was roughly equal to the tear strength at the same rate. The failure, even in this case, propagated smoothly at the interface, showing that it remains 14 who studied autohesion of polybutadienes. This evolution can be explained by the decrease of the quantity of peroxide available for co-crosslinking when the precure time becomes longer.…”
Section: Influence Of the Pre-cure Timementioning
confidence: 81%